MACHINE LEARNING SERVICE FOR STUDENT REGISTRATION - Točelovskis, Andrejs; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The paper provides various tips for machine learning tehnology. The main part describes main functionality of machine learning service for human face recognition